Pengaruh Food Quality dan Ketersediaan Produk Terhadap Repurchase Intention Produk Sari Roti di Surabaya - Stanley Muliawan (Jurnal Strategi Pemasaran, 2018)
The growing cake and bakery industry makes more and more players entering the industry, requiring a strategy to sustain consumers. This study aims to analyze the effect of food quality and product availability on repurchase intention of Sari Roti products in Surabaya. This study was conducted by distributing questionnaires to 100 respondents on consumers who have made transactions of Sari Roti products in Surabaya. This type of research uses data processing from Smart PLS 3.0. The results of this study indicate that food quality has significant effect on repurchase intention; and product availability have a significant effect on repurchase intention.